Truncated Variants in FAM20A and WDR72 Genes Underlie Autosomal Recessive Amelogenesis Imperfecta in Four Pakistani Families - Sadaqat Ullah; Sher Alam Khan; Samin Jan; Salah Ud Din; Nazif Muhammad; Zia Ur Rehman; Abid Jan; Muhammad Tariq; Noor Muhammad; Abdul Ghani; Naveed Wasif; Saadullah Khan (Biochemical Genetics, 2026)
Amelogenesis Imperfecta (AI) is a set of hereditary diseases affecting enamel development, leading to various types of enamel defects, potentially impacting oral health unassociated with other generalized defects. AI manifests in syndromic and non-syndromic forms and can be inherited through autosomal recessive, autosomal dominant, or X-linked inheritance patterns. Genetic studies have identified sequence variants in a number of genes (≥ 70) linked to both syndromic and non-syndromic AI, highlighting the genetic diversity underlying the condition. The current study involved clinical evaluation and exome sequencing, aimed at identifying the causative variants in four unrelated consanguineous Pakistani families presenting AI phenotypes. The exome sequencing results revealed a novel homozygous frameshift variant FAM20A : NM_017565.4, c.188dupA; p.(Asp63Glufs*17) in families A, B, and C while a nonsense homozygous variant WDR72 : NM_182758.4, c.2686C > T; p. (Arg896*) in family D. The segregation of both variants was confirmed by Sanger sequencing. Bioinformatics analysis predicted the pathogenicity of these genetic variants. These alterations suggest functional consequences, potentially impairing the FAM20A and WDR72 proteins and causing dental anomalies. This investigation significantly broadens our understanding of FAM20A and WDR72 ’s involvement in AI. Furthermore, this study highlights the genetic heterogeneity of AI (involving FAM20A and WDR72 in this study) within the Pakistani population.

Mitigating energy risk through energy sources diversification - Arusha Cooray; Muhammad Shahbaz; Bekhzod Kuziboev; A. Nazif Çatık (Journal of Environmental Management, 2025)

Evaluating the biological activity of rolB-transgenic Nicotiana tabacum plants using phytochemical and pharmacological approaches - Afshan Anwar; Shabana Haneef; Hammad Ismail; Muhammad Zeeshan Bhatti; Nazif Ullah; Iram Murtaza; Bushra Mirza (Plant Biosystems, 2024)